2014
DOI: 10.1186/preaccept-2009606419137811
|View full text |Cite
|
Sign up to set email alerts
|

Notch signaling in serous ovarian cancer

Abstract: Ovarian cancer is the most lethal of all gynecologic malignancies because women commonly present with advanced stage disease and develop chemotherapy refractory tumors. While cytoreductive surgery followed by platinum based chemotherapy are initially effective, ovarian tumors have a high propensity to recur highlighting the distinct need for novel therapeutics to improve outcomes for affected women. The Notch signaling pathway plays an established role in embryologic development and deregulation of this signal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
31
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(35 citation statements)
references
References 88 publications
(93 reference statements)
3
31
1
Order By: Relevance
“…NOTCH signaling participates in TIC fate in gliomas (Fan et al, 2006) and lung cancer (Sullivan et al, 2010; Zheng et al, 2013). GSI inhibitors of NOTCH exhibit potent anti-tumor activity in glioma (Fan et al, 2010; Fan et al, 2006), lung (Konishi et al, 2007), and ovarian cancers (Groeneweg et al, 2014a; Groeneweg et al, 2014b) and the potent GSI PF-03084014 has shown clinical promise in advanced cancer patients (Messersmith et al, 2015). The anti-rheumatoid gold salts ATM and ANF selectively inhibit PKCι signaling and block growth of lung (Erdogan et al, 2006; Fields et al, 2007; Regala et al, 2008; Stallings-Mann et al, 2006), pancreatic (Butler et al, 2015; Scotti et al, 2012) and ovarian (Wang et al, 2013) tumors in vitro and in vivo , and two clinical studies have demonstrated proof-of-principle for PKCι inhibitor-based therapy with ATM (Mansfield et al, 2013) and ANF (Jatoi et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…NOTCH signaling participates in TIC fate in gliomas (Fan et al, 2006) and lung cancer (Sullivan et al, 2010; Zheng et al, 2013). GSI inhibitors of NOTCH exhibit potent anti-tumor activity in glioma (Fan et al, 2010; Fan et al, 2006), lung (Konishi et al, 2007), and ovarian cancers (Groeneweg et al, 2014a; Groeneweg et al, 2014b) and the potent GSI PF-03084014 has shown clinical promise in advanced cancer patients (Messersmith et al, 2015). The anti-rheumatoid gold salts ATM and ANF selectively inhibit PKCι signaling and block growth of lung (Erdogan et al, 2006; Fields et al, 2007; Regala et al, 2008; Stallings-Mann et al, 2006), pancreatic (Butler et al, 2015; Scotti et al, 2012) and ovarian (Wang et al, 2013) tumors in vitro and in vivo , and two clinical studies have demonstrated proof-of-principle for PKCι inhibitor-based therapy with ATM (Mansfield et al, 2013) and ANF (Jatoi et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…Previously, it was reported that OVCAR3, SKOV3, and CaOV3 cells, as well as a large portion (76%) of human ovarian papillary serous adenocarcinomas, express NICD, which is a potential target for new drug therapies in ovarian cancer [25]. Notch signaling is also a potential diagnostic marker of epithelial ovarian cancer [26]. Up-regulation of the Notch3 and increased expression of the Jagged2 was reported in ovarian cancers [27, 28].…”
Section: Discussionmentioning
confidence: 99%
“…Disruption of Notch signaling results in multiple human diseases including Alagille syndrome (Oda et al 1997), familial aortic valve disease (Garg et al 2005), Adams-Oliver syndrome (Stittrich et al 2014), Hajdu-Cheney syndrome (Simpson et al 2011), spondylocostal dysostosis (Bulman et al 2000), cerebral autosomal dominant arteriopathy with subcortical infarcts and leukoencephalopathy (CADASIL) (Joutel et al 1996), Alzheimer disease (Kopan & Goate 2000), and cancers including T-cell acute lymphoblastic leukemia (Weng et al 2004) and pancreatic (Mullendore et al 2009), colon (Reedijk et al 2008), and ovarian cancers (Groeneweg et al 2014). …”
Section: Notch Pathway Signal Transduction and Regulationmentioning
confidence: 99%
“…Alterations in the expression of Notch pathway genes has also been correlated with ovarian cancers that develop resistance to treatment (Groeneweg et al 2014); however, it is unclear by what means aberrant Notch signaling may facilitate the survival of cancer cells. Difficulty in treating ovarian tumors has at least in part been attributed to the formation or maintenance of cancer stem cells (Jordan et al 2006, Shah et al 2013, Walters Haygood et al 2014).…”
Section: Role Of Notch Signaling In the Human Ovarymentioning
confidence: 99%
See 1 more Smart Citation